Dari Scroll to Checkout: Live Streaming, FOMO, dan Impulse Buying Mahasiswa FISIP Universitas Sumatera Utara di TikTok Shop - Annisa Putri Arneliani; Christian Frizy Haloho; Feby Emanuela Karo Karo; Jorenta Ginting; Renata Florenika Br Sembiring; Onan Marakali Siregar; Ummi Salamah Sitorus (Yayasan Sagita Akademia Maju, 2026)
This study analyzes the influence of live streaming and Fear of Missing Out (FOMO) on impulsive purchases among students of the Faculty of Social and Political Sciences (FISIP) at the University of North Sumatra who are TikTok Shop users. The development of social commerce through TikTok Shop has driven changes in consumer behavior, especially among students, in making spontaneous purchases due to digital interactions and emotional impulses. This study is quantitative with an associative causality design. The population includes active FISIP students from the 2022–2025 intake who use TikTok Shop, with a sample of 100 respondents selected through purposive sampling. Data were collected through an online questionnaire based on a 5-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results showed that FOMO had a positive and significant influence on impulsive purchases (t-statistic = 9.570; p < 0.001), as did live streaming (t-statistic = 2.927; p < 0.003). The higher the FOMO and engagement in live streaming, the greater the tendency to make impulse purchases. This research contributes to the study of digital consumer behavior, specifically social commerce and impulse buying among college students. The findings suggest that students' impulse purchases on TikTok Shop are influenced not only by the interactive features of live streaming but also by psychological pressures such as the fear of missing out on opportunities, trends, or limited promotions.